Aquatic ecosystem responses to environmental and climatic changes in NE China since the last deglaciation (∼17, 500 cal yr BP) tracked by diatom assemblages from Lake Moon. (15th November 2021) - Chen, Jie; Liu, Jianbao; Rühland, Kathleen M.; Smol, John P.; Zhang, Xiaosen; Zhang, Zhiping; Zhou, Aifeng; Shen, Zhongwei; Chen, Fahu
Abstract: The scarcity of research in NE China on lake ecosystem responses to large-scale climate oscillations since the last deglaciation limits our abilities for informing conservation practices and policies in the context of recent global warming. Here, a high-resolution, sedimentary diatom record covering the past ∼17, 500 years was retrieved from Lake Moon, a small, hydrologically closed crater lake in the remote central part of the Great Khingan Mountain Range in NE China. We compare diatom changes with geochemical data from the same core, and with regional palynological and dust deposition records, to better understand the influences of long-term environmental and climatic variability on aquatic ecosystems in this climatically sensitive region. Several abrupt and pronounced shifts in dominance among diatom taxa corresponded to marked fluctuations in the climate regime since the last deglaciation. During the close of the Last Glacial Period, a series of short-lived diatom shifts that were indicative of an increase in nutrients, signaled the transition from the cold period of the Heinrich event 1 (∼17, 500–∼14, 700 cal yr BP) to the warmer Bølling - Allerød interstadial period (∼14, 700–∼12, 900 cal yr BP). The onset of the cold Younger Dryas period was marked by a brief rise to dominance of benthic taxa (∼12, 900–∼11, 800 cal yr BP), followed by a pronounced lake ecosystem shift to a new trophic state at the Pleistocene-Holocene transition (∼11, 800–∼9900 cal yr BP), evidenced by an abrupt rise to dominance of several eutrophic diatom indicators (e.g. Cyclostephanos dubius, Aulacoseira ambigua and Stephanodiscus parvus ). This nearly complete compositional turnover was indicative of an increase in phosphorus supply to the lake with the onset of a warmer and moister climate and an increased frequency of strong dust storms. During the mid-Holocene (∼6000 cal yr BP), a striking increase in the relative abundance of Discostella pseudostelligera and Asterionella formosa, at the expense of previously dominant eutrophic indicators, signified another lake ecosystem change from well-mixed, turbid and phosphorus-rich conditions to a lower nutrient state with longer open-water periods and increased thermal stability. The turnover to oligotrophic diatom taxa was likely in response to variations in seasonal temperature, precipitation and dust deposition. The diatom shifts of Lake Moon during the past ∼17, 500 years were directly or indirectly mediated by climate change that affected thermal stratification, productivity, lake level and trophic state. Our results indicate that climate change had an overarching control on aquatic ecosystem changes in the mountain regions of NE China since the last deglaciation. Highlights: A continuous diatom record tracking aquatic ecosystem dynamics in NE China since the last deglaciation. Significant ecological reorganizations corresponded to the Heinrich 1 event, the Bølling - Allerød interstadial and the Younger Dryas. Aquatic ecosystem during the Holocene responded to seasonal variations in temperature, precipitation and dust deposition. Climate change and its mediating effects on landscape processes had an overarching control on aquatic ecosystem changes.